Factors influencing the amount of therapy received during inpatient stroke care: an analysis of data from the UK Sentinel Stroke National Audit Programme. (July 2020) - Gittins, Matthew; Vail, Andy; Bowen, Audrey; Lugo-Palacios, David; Paley, Lizz; Bray, Benjamin; Gannon, Brenda; Tyson, Sarah
Objectives: To understand why most stroke patients receive little therapy. We investigated the factors associated with the amount of stroke therapy delivered. Methods: Data regarding adults admitted to hospital with stroke for at least 72 hours (July 2013–July 2015) were extracted from the UK's Sentinel Stroke National Audit Programme. Descriptive statistics and multilevel mixed effects regression models explored the factors that influenced the amount of therapy received while adjusting for confounding. Results: Of the 94, 905 patients in the study cohort (mean age: 76 (SD: 13.2) years, 78% had a mild or moderate severity stroke. In all, 92% required physiotherapy, 87% required occupational therapy, 57% required speech therapy but only 5% were considered to need psychology. The average amount of therapy ranged from 2 minutes (psychology) to 14 minutes (physiotherapy) per day of inpatient stay. Unmodifiable characteristics (such as stroke severity) dominated the variation in the amount of therapy. However important, modifiable organizational factors were the day and time of admission, type of stroke team, timely therapy assessments, therapy and nursing staffing levels (qualified and support staff), and presence of weekend or early supported discharge services. Conclusion: The amount of stroke therapy is associated with unmodifiable patient-related characteristics and modifiable organizational factors in that more therapy was associated with higher therapy and nurse staffing levels, specialist stroke rehabilitation services, timely therapy assessments, and the presence of weekend and early discharge services.